ANALYZING MOTIVATED READERS: A READER-RESPONSE STUDY ON A. FUADI’S THE LAND OF FIVE TOWERS - LASARI, NADIA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: reader-response, motivation, The Land of Five Towers, Forum LingkarPena Malang A literary work is produced by a writer not only to entertain but also to deliver a message. The example of the message contained in a literary work is motivation to gain some goals or dreams. A. Fuadi’s The Land of Five Towers novel is one of literary works which carries out motivation as its subject.This research applies reader-response theory, specifically transactional reader-response and theory of motivation to find out the number of motivated and unmotivated readers and what are the motivations gained after reading The Land of Five Towers. Besides, this research also applies both quantitative and qualitative approach through numbers and document analysis to examine the data taken from the questionnaire, the interview and the novel. In this case, the respondents of the research is the members of Forum Lingkar Pena Malang.The data is taken  from questionnaire distributed to 40 (forty) respondents, they are members of Forum Lingkar Pena Malang. All of the respondents or 100% are motivated and 0% unmotivated after reading The Land of Five Towers. The motivations gained by the readers are classified into 7 (seven) categories. Those categories are motivation to study abroad and get better education, motivation to improve and learn deeper one’s passion, motivation to make parents proud, motivation to work harder than before, motivation to be successful in career or work, and motivation to maintain a good and long-last friendship. Some motivational parts in this novel are A- Half Hearted Decision, Hundreds of Thousands of Handshakes, Mice Meeting, Man Jadda Wajada, Five Countries Four Continents, Fellowship of The Manara, Tyson’s First Attack, Inner War, and Trafalgar Square.